FEEDING AND REPRODUCTIVE ACTIVITY OF THE COPEPODS Drepanopus forcipatus AND Calanus australis DURING LATE SUMMER ON THE SOUTHERN PATAGONIAN SHELF (ARGENTINA, 47°-55°S) - Julieta Carolina Antacli; Marina E. Sabatini; Ricardo I. Silva; Daniel R. Hernández; Andrés J. Jaureguizar; Rut Akselman (Brazilian Journal of Oceanography, 2014)
Drepanopus forcipatus and Calanus australis are key planktonic copepods on the southern Patagonian shelf. Their feeding and reproductive patterns and population status were investigated during late summer, when environmental conditions may be critical. The presence of food in the gut and food-pellet length were recorded in adult females and the most abundant copepodite stages. Diet composition was also studied in adult females. Female reproductive status was evaluated by gonad staging. Despite generally low feeding conditions and decreasing seasonal temperature, both copepods fed to some degree. The most numerous copepodites and adult females of both species showed similarly low feeding activity. About half of the adult females of the two species and C5s of C. australis contained food in their guts, but the proportion of fed C4-females of D. forcipatus was much lower. All copepods were generally feeding at low or intermediate levels. Gonad stage distribution and population structure showed low but still ongoing reproduction in both species. Gut content findings suggest a preference for smaller nanoplanktonic particles, especially dinoflagellates by D. forcipatus, and for autotrophic prey, particularly large diatoms by C. australis. The feeding and reproduction patterns of the two copepods were likely influenced by the distributions of potential food resources and temperature.